Bilateral Extracranial Internal Carotid Artery Dissection: Interventional Management – A Case Report - Sasannejad, Payam; Khanmirzaei, Amir; Soltani, Mohsen; Karimikhoshnoudian, Bahar; Gorji, Reza; Baharvahdat, Houman; Shakib, Soheil Shokri; Payere, Maryam (Brazilian Journal of Case Reports, 2024)
Traumatic internal carotid artery dissection (ICAD), particularly in bilateral cases, is a rare but life-threatening condition that poses diagnostic and therapeutic challenges. The cervical segment of the internal carotid artery (ICA) is especially vulnerable to injury following blunt trauma, often leading to significant neurological sequelae. Despite established guidelines advocating conservative management as the initial approach, the optimal timing and criteria for endovascular intervention remain areas of ongoing investigation. We report the case of a 38-year-old female who presented with bilateral extracranial ICAD following a motor vehicle accident. Initially, the patient exhibited right hemiparesis and aphasia, and imaging confirmed left extracranial ICAD without critical stenosis or pseudoaneurysm formation. Conservative management with dual antiplatelet therapy was guided by imaging findings and risk assessment and led to temporary symptomatic improvement. However, the patient returned on the eighth day with left hemiplegia and loss of consciousness, prompting further imaging that revealed bilateral dissection and right anterior cerebral artery infarction. Given the failure of medical therapy, endovascular stenting was performed, achieving successful revascularization and symptomatic improvement. The management of traumatic ICAD, particularly bilateral cases, necessitates careful risk assessment and timely intervention. Our case highlights the importance of imaging in guiding the decision-making process and balancing conservative versus invasive management strategies. Endovascular stenting, although effective, should be reserved for cases with progressive symptoms or when medical management fails. This report contributes to the limited literature on bilateral traumatic ICAD and underscores the need for further research to establish evidence-based guidelines for the management of such cases. Future studies should compare the outcomes of conservative, surgical, and endovascular interventions to optimize patient care and improve prognostic outcomes.